Sodobni pristopi k organiziranosti zdravstvene nege: procesna organizacija - Kamenšek, Petra (Obzornik zdravstvene nege, 2004)
The article presents the model of process organization of the system of nursing care, together with issues of management and requirements of the performers of health care. The essential feature of the process organization is the adaptation staff and organizational structure to the requirements of individual processes, and not vice versa. It can happen that less adapted structures to the processes, the latter become rigid and inflexible, and the borders among departments and fucntions more outstanding. Process orientation requires a generalized, holistic approach to the user of the services of nursing care which reaches beyond specialization.
Keywords: Health Care; Marketing Of Health Services; Negovalne službe; Nursing Care; Nursing Process; Nursing Services; organizacija zdravstva; Organization And Administration; Postopek, ocenjevanje (zdravstveno varstvo); Process Assessment (Health Care); Trženje zdravstvenih služb; zdravstvena dejavnost; Zdravstvena nega; Zdravstvena nega, proces